Risk Factors for the Occurrence of ARI in Toddlers in Densely Populated Environments - Septi Viantri Kurdaningsih; Zola Efa Harnis; Lilik Septiana; Rahayu Tri Nuritasari (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
Acute respiratory infection (ARI) is one of the diseases that often affects toddlers, especially in densely populated environments that have a high risk of transmission. Purpose: this study aims to analyze the risk factors for the occurrence of ARI in children under five who live in an environment with high population density. Methods: the method used is observational with cross-sectional design on 50 toddlers purposively selected in densely populated areas. Data collection was conducted through interviews using questionnaires and observation of Home environmental conditions. Univariate analysis was used to describe the characteristics of respondents, while bivariate analysis with chi-square test was used to determine the relationship between risk factors with the incidence of ARI. Results: the results showed that exposure to cigarette smoke in the Home (p = 0.005), inadequate ventilation (p = 0.002), and density of occupancy (p = 0.020) were significantly associated with the incidence of ARI in toddlers. Implications: the implication of this study is the need for increased family education on the importance of a healthy home environment and reduced exposure to secondhand smoke to prevent ARI. Conclusion: environmental factors and family behavior are the main determinants of ARI risk in toddlers in densely populated environments, so environmental health interventions and health education are needed.